Correlation between Organizational Culturewith Clinical Governance in Public Hospitals in Rasht - Seyed Mohammad Mirkamali; Mandana Javanak Liavali; Mohammad Reza Yeganeh (Tehran University of Medical Sciences, 2014)
Background & Aim: The quality of clinical services is a major concern for healthcare systems throughout the world. Clinical Governance, a relatively new approach to improve quality of healthcare systems, plays a fundamental role in the establishment of primary healthcare strategies to provide high quality services. Moreover, regarding the importance of organizational culture as a powerful lever to improve organizational behavior, success of organizations in implementing strategies largely depends on the support receiving from organization. Accordingly the aim of this study was to examine the correlation between organizational culture with establishment of clinical governance in public hospitals in Rasht .   Methods & Materials: A cross-sectional correlation study with structural equation modeling was used. All 152 nurses working in managerial positions participated in the study. Data were collected using Denison Organizational Culture questionnaire, and research-made questionnaire on clinical governance. Validity and reliability of questionnaire were confirmed. Data were analyzed using the Pearson correlation coefficient test and confirmatory factor analysis in the SPSS and LISREL .   Results: There was a significant positive relationship between clinical governance and all components of organizational culture (P< 120.01' type="#_x0000_t75"> ). Factor analysis showed the impactof organizational culture on successful establishment of clinical governance .   Conclusion: Improvement of organizational culture leads to sustainable establishment of clinical governance; through which quality of healthcare services improves. Managers of hospitals should pay attention to instituting appropriate organizational culture in order to establish clinical governance .